Pengaruh Islamic Work Ethic terhadap Counterproductive Work Behavior pada Guru Lembaga Pendidikan Pondok Pesantren - Fikar Aulia Muhammad; Lisa Widawati; Ayu Tuty Utami (UNISBA Press, 2024)
Abstract. Organizational progress and development in the education sector is often hampered by the problem of counterproductive work behavior shown by teachers which is detrimental to the organization and to the personnel within it. Counterproductive work behavior can be prevented by understanding a work ethic in every employee, a work ethic that is relevant to the majority of Indonesian people who are Muslim is the existence of an Islamic work ethic. Islamic boarding schools as religious-based educational institutions certainly have an Islamic work ethic that can reduce counterproductive work behavior. The purpose of this research is to obtain empirical data regarding the influence of Islamic work ethic on Counterproductive Work Behavior in Teachers of Islamic Boarding Schools. This research was conducted using a non-experimental quantitative method with a causality design involving 164 Islamic boarding school teachers in Bandung Raya as respondents. The measuring instrument used to measure Islamic work ethic is the Islamic work ethic Scales compiled by Ali (1992) which was adapted into Indonesian by Firmansyah et al. (2020) which was again adapted by the author. The Counterproductive Work Behavior variable uses the Counterproductive Work Behavior Checklist (CWB-C) published by Spector et al. (2006) and adapted by Cucuani et al. (2020). The results of this study indicate that Islamic work ethic has a negative effect of 63.2% on Counterproductive Work Behavior. Abstrak. Kemajuan dan perkembangan organisasi pada sektor pendidikan seringkali dihalangi oleh permasalahan adanya perilaku kontraproduktif yang ditunjukkan oleh guru yang merugikan organisasi dan personal di dalamnya. Perilaku kontraproduktif dapat dicegah dengan menanamkan etos kerja pada setiap karyawan, etos kerja yang relevan dengan mayoritas masyarakat Indonesia yang beragama islam adalah dengan adanya etos kerja Islami. Pondok pesantren sebagai lembaga pendidikan berbasis agama tentu memiliki etos kerja islami yang dapat mengurangi adanya perilaku kontraproduktif. Adapun tujuan dari penelitian ini adalah untuk memperoleh data empiris mengenai pengaruh Islamic work ethic terhadap counterproductive work behavior pada Guru Lembaga Pendidikan Pondok Pesantren. Penelitian ini dilakukan dengan menggunakan metode kuantitatif non-eksperimental dengan desain kausalitas yang melibatkan 164 guru pondok pesantren se bandung raya sebagai responden. Alat ukur yang digunakan untuk mengukur islamic work ethic adalah islamic work ethic Scales yang disusun oleh Ali (1992) yang diadaptasi kedalam Bahasa Indonesia oleh Firmansyah et al. (2020) yang kembali diadaptasi oleh penulis. Untuk variable counterproductive work behavior menggunakan alat ukur counterproductive work behavior Checklist (CWB-C) yang dipublikasikan oleh Spector et al. (2006) dan diadaptasi oleh Cucuani et al. (2020). Hasil Penelitian ini menunjukkan bahwa islamic work ethic berpengaruh negatif sebesar 63,2% pada counterproductive work behavior.